Analysis of genetic effects of major genes on yield traits of a pea (pisum sativum l.) cross between the santa isabel x wsu 31 varieties (2012)
Análisis de efectos de genes mayores sobre rasgos de rendimiento en arveja (Pisum Generation means and heritability analyses were conducted to estimate dominance, additive, maternal and gene interaction effects controlling eleven agronomic characteristics related with production in the pea. Ten generations (P1, P2, F1, F2, RC1, RC2 and each reciprocal generation) from a cross between the Santa Isabel and WSU 31 varieties were sown in two different environments for the present study. Eleven characteristics were evaluated: the time between sowing and flowering (I), the time between sowing and pod formation in the first reproductive node (FPod) and the height of the first reproductive node (H1RN), which were used as earliness indicators; as components of yield, the number of pods per plant (PxP), number of seeds per plant (SxP), number of seeds per pods (SxPod) and 100-seed weight (W100) were evaluated; and as variables associated to the yield, the pod width (PW), pod length (PL), lateral branch number (LBN) and plant height (PH) were evaluated. The results did not show maternal gene effects for the evaluated traits; environmental effects were found in PxP, SxP, SxPod, SFl, FPod and PL; genotype x environment effects were found in PW and W100. All characteristics except SxP and PxP had additive gene effects. The results showed that W100, PW and PL were the characteristics with the highest values for selection.